2018
DOI: 10.1002/1873-3468.13193
|View full text |Cite
|
Sign up to set email alerts
|

Models of synaptotagmin‐1 to trigger Ca2+‐dependent vesicle fusion

Abstract: Vesicles in neurons and neuroendocrine cells store neurotransmitters and peptide hormones, which are released by vesicle fusion in response to Ca -evoking stimuli. Synaptotagmin-1 (Syt1), a Ca sensor, mediates ultrafast exocytosis in neurons and neuroendocrine cells. After vesicle docking, Syt1 has two main groups of binding partners: anionic phospholipids and the SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptors) complex. The molecular mechanisms by which Syt1 triggers vesicle fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 120 publications
(236 reference statements)
3
58
0
Order By: Relevance
“…A central assumption of our model is that activation of Syt1 by Ca 2+ binding lowers the fusion barrier ( Ruiter et al, 2019 ; Jackman and Regehr, 2017 ; Pérez-Lara et al, 2016 ; Park and Ryu, 2018 ). Several competing models have been proposed for this ( Park and Ryu, 2018 ). Both the Syt1 D232N mutant, where Ca 2+ -binding is mimicked, and the Syt1 4W mutant where hydrophobicity is increased, showed increased spontaneous and HS-induced release rates up to 250 mM HS, in line with a reduced fusion energy barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A central assumption of our model is that activation of Syt1 by Ca 2+ binding lowers the fusion barrier ( Ruiter et al, 2019 ; Jackman and Regehr, 2017 ; Pérez-Lara et al, 2016 ; Park and Ryu, 2018 ). Several competing models have been proposed for this ( Park and Ryu, 2018 ). Both the Syt1 D232N mutant, where Ca 2+ -binding is mimicked, and the Syt1 4W mutant where hydrophobicity is increased, showed increased spontaneous and HS-induced release rates up to 250 mM HS, in line with a reduced fusion energy barrier.…”
Section: Discussionmentioning
confidence: 99%
“…A central assumption of our model is that activation of Syt1 by Ca 2+ binding lowers the fusion barrier [5,27,65,66]. Several competing models have been proposed for this [66].…”
Section: Activation Of Syt1's Ca 2+ Binding Domain Decreases the Fusimentioning
confidence: 99%
“… 156 It is a transmembrane protein anchored in the vesicle membranes containing 2 Ca 2+ -binding domains. In response to Ca 2+ -binding at elevated concentrations, synaptotagmin-1 triggers the vesicle fusion, but the exact molecular mechanisms remain to be elucidated (for review see Park and Ryu 157 ). Initial CSF studies of synaptotagmin-1 found it to be decreased in a CSF pool from patients with early-onset AD compared with a CSF pool from healthy controls.…”
Section: Fluid Biomarkers For Synapse Pathologymentioning
confidence: 99%
“…In the Rothman buttressed ring model , synaptotagmin‐1 oligomerizes into a ring with other components of the fusion machinery that rapidly dissociates upon calcium binding. In this Special Issue, Park and Ryu discuss the ring model, as well as other models of synaptotagmin‐1 function. Garcia‐Martinez et al .…”
mentioning
confidence: 99%
“…In the Rothman buttressed ring model [4], synaptotagmin-1 oligomerizes into a ring with other components of the fusion machinery that rapidly dissociates upon calcium binding. In this Special Issue, Park and Ryu [8] discuss the ring model, as well as other models of synaptotagmin-1 function. Garcia-Martinez et al [9] review lipids that modulate exocytosis through various mechanisms, including recruitment of fusion proteins to specific sites, modulation of local membrane properties or lipidation of key fusion proteins.…”
mentioning
confidence: 99%